Family Nutrition Management Using Rice Bran Milk to Prevent Stunting - Chandra Dewi Sagala, Anita; Umiyati, Rini; Karmila, Mila; Indah Permata Sary, Oktavia (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This study aimed to analyze family nutrition management through the utilization of rice bran milk in preventing stunting among children aged 4–6 years. The study employed a Research and Development design using the Analysis, Design, Development, and Implementation model. The subjects consisted of 30 families in Mranggen District, Demak Regency, selected through purposive sampling. Data were collected through observation, a family nutrition management questionnaire, and measurements of children’s nutritional status based on body mass index for age. The data were analyzed using descriptive quantitative analysis followed by simple linear regression testing. The results indicated that 36.67% of families demonstrated very good nutrition management, 36.67% good, and 26.66% poor. The majority of children (63.33%) had normal nutritional status, while 10% were underweight, 20% overweight, and 6.67% obese. Regression analysis showed a significance value of 0.001, indicating a significant influence of family nutrition management on children’s nutritional status. The implementation of training programs and regular consumption of rice bran milk demonstrated potential as a functional local food alternative to support children’s nutritional intake. The findings concluded that systematic family nutrition management supported by the utilization of rice bran milk contributed to maintaining and improving children’s nutritional status as an effort to prevent stunting.